INSPECTION AND DIVERSITY ON SIAM ORANGE PLANTS (Citrus nobilis l.) - Tustiyani, Isna; Maesyaroh, Siti Syarah; Dewi, Tinah Kartika; Mutakin, Jenal (Jurnal Pertanian, 2018)
The research was conducted to determine the diversity of species and the role of insects between pests and natural enemies insect in siamese orange (Citrus nobilis l.). Observation was done in Karangsari villege, Karangpawitan subdistrick, Garut districk from April to Jone 2018. The method used in qualitative method in five different land basedon the age of siamese orange plants (Citrus nobilis l.) where on the first and seccond field of the plant age 1,5 years, the third land the plant age of 2,5 years, the fourth land the age of the plant 4 years,  and on the fifth is the age of 8 months of plant life which concists of 2 observation, that is observation using yellow trap and visual observation at 5 sample points of siamese orange (Citrus nobilis l.). The results showed that the insects found in citrus (Citrus nobilis l.) plants consisted of 9 orders and conculated using the diversity index and dominance index. Insects found from five different fields, generally insect pests are the highest compared to natural enemies. The highest insects populations is on experiental land 5  with 8 moths of plant life and diversity index on five fields of siamese orange  (Citrus nobilis l.) planting has a moderate measure value and a low dominance index.